Effect of heat treatment on hardness of modified spring steel material - Maumela Mbavhalelo; Mkhonto Donald; Mathabathe M. N.; Phasha Maje (MATEC Web of Conferences)
Spring steel materials are mainly used for semi-static loading applications. In addition, they provide a proper suspension of engineering structures in order to maintain their structural integrity. In order to meet properties required for engineering service, spring should be able to deform elastically during loading and return to its original shape upon unloading, without any plastic deformation or fracture. A plastic deformation alters the structural integrity, resulting in a loss of spring functionality. Since hardness is one of required primary properties of spring steel, this study conducted several heat treatment designs to optimize hardness of altered spring steel material. Microstructures were acquired and analysed using an optical microscope. A suggested approach for heat treatment design is recommended for engineering applications.